SCIENCE TALK IN THE SECONDARY CLASSROOMS: ANALYSIS OF TEACHERS’ FEEDBACK - Siddiquee, Muhammad Nur-E-Alam; Ikeda, Hideo (European Scientific Journal, ESJ, 2013)
Feedback, the third part of Initiation-Response-Feedback (IRF) structure in typical lesson discussion, is the most crucial part of teaching and science talk. Feedback constructs cognitive scaffolding as well as dialogical pattern of discussion in the classroom. Several studies analyzing teachers’ feedback types and wait time of effect have been reported. Owing to its tremendous effect on teaching and learning, as stated by Chin (2007), a fine grained analysis has been felt. Video recorded data of fourteen science lessons in secondary level (Grade VI-X) of Bangladesh used as data source of this study. Data were analyzed with coded category. Through video analysis, the nine categories of teachers’ feedback were emerged to students’ correct and incorrect or no response. The prevalent nature of feedback was evaluative and corrective. All the generated categories were illustrated with example taken from the real lesson and tried to explain the effect of each type of feedback on lesson discussion. The results of the study are illustrated vignettes of the teachers’ varieties of feedback and the role of the feedback at secondary science lessons, and would be helpful for teachers to think and frame their practices that make a science lesson into collaborative, dialogic and facilitative one.